From Volmar to Omsk by roads of service: to the biography of State Councilor G. Ya. Galkin (1861–1919) - L. A. Bodrova; D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The study, built on correlating a complex of unpublished sources and oral family history, for the first time reconstructed the life path of G. Ya. Galkin, a civilian official, holder of 12 orders and medals, chief of Omsk, then Amur post and telegraph districts. During the period of the active introduction of telegraph in Russia, he served from an ordinary practitioner to a senior manager. The biographical method became the main one in writing the article, based on its scientific genre. The authors attempted to analyze the historical conditions and factors that influenced the personal and professional development of the hero of the publication